If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + -22 = -3(x + -1) Reorder the terms: -22 + -8x = -3(x + -1) Reorder the terms: -22 + -8x = -3(-1 + x) -22 + -8x = (-1 * -3 + x * -3) -22 + -8x = (3 + -3x) Solving -22 + -8x = 3 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -22 + -8x + 3x = 3 + -3x + 3x Combine like terms: -8x + 3x = -5x -22 + -5x = 3 + -3x + 3x Combine like terms: -3x + 3x = 0 -22 + -5x = 3 + 0 -22 + -5x = 3 Add '22' to each side of the equation. -22 + 22 + -5x = 3 + 22 Combine like terms: -22 + 22 = 0 0 + -5x = 3 + 22 -5x = 3 + 22 Combine like terms: 3 + 22 = 25 -5x = 25 Divide each side by '-5'. x = -5 Simplifying x = -5
| 4x+17=90 | | 2f+20=101-f | | 2w-18w=-32 | | 32+12y=420 | | 78=3c+12+-1c+4 | | -139=5x+7+5 | | x-38=84 | | 3m+167=55+4m | | 12y+22=9y | | 3x(x+20)=44 | | -11+8x=-67 | | -2p+28=6p-44 | | -6(x+2)-13=10+1 | | (-10x+35)*(5)=x | | 9t=42 | | 9(-8)-4((-8)-7)= | | -2x+7+7x=-3 | | -65+2x=33-5x | | 7c-4c=78+12 | | 34-5x=-21 | | 6y-90=5y-75 | | 5(t-6)+5t=5(2t+2)-9 | | (-10x+35)*(5)= | | (6-2c)+(3c-4)= | | 0.5+0.7=-0.75 | | 4h=5h-60 | | 3x+18=4x+13 | | y=(2t(5-t)) | | 150m-100m+42750=45450-175m | | 3m+167=4m+55 | | 21=6+x+-4x | | 2.3p=46 |